Organ Dysfunctions due to Covid-19 (Research, Society and Development, 2023)
The aim of this study is to conduct a narrative review of the literature to better understand the extensive pathological effect of Covid-19 on vital organs and to point out new updates on the subject. The world has been impacted by the coronavirus disease 2019 pandemic, a severe acute respiratory syndrome caused by the SARS-CoV-2 coronavirus. Organic dysfunctions present as alterations or loss of the normal functions of vital organs and systems of the human body, which can lead to the failure of multiple organs. Although Covid-19 presents primarily as a respiratory tract infection transmitted by air droplets, growing data suggest multi-organ involvement. SARS-CoV-2 has as its mechanism of infection the binding of the viral protein to the ECA2 receptor, which facilitates the spread of the virus through the vascular system. Accumulated evidence indicates that patients who have developed Covid-19 may present in addition to airway compromise, neurological, cardiac, renal, metabolic and intestinal symptoms accompanied by a deficient and ineffective immune response, however, new searches are crucial to better understand its etiology.